Teachers’ Emotional Exhaustion: Associations With Their Typical Use of and Implicit Attitudes Toward Emotion Regulation Strategies - Donker, Monika H.; Erisman, Marja C.; van Gog, Tamara; Mainhard, Tim (Frontiers in Psychology, 2020)
Teaching is an emotionally challenging profession, sometimes resulting in high levels of teacher stress, burnout, and attrition. It has often been claimed that certain emotion regulation strategies can lower teachers’ feelings of burnout. The use of cognitive reappraisal (i.e., cognitively changing the emotional impact of a situation) has generally been associated with positive outcomes, whereas using expressive suppression (i.e., inhibiting emotional responses) usually has negative consequences. The present study investigated the association between teachers’ typical use of these two emotion regulation strategies (i.e., cognitive reappraisal and expressive suppression) and their feelings of emotional exhaustion. Because there is evidence that regulating emotions could involve higher costs when regulation goes against individual preferences, we also explored the potentially moderating effect of teachers’ implicit attitudes towards emotion regulation versus emotion expression on the association between typical use of emotion regulation strategies and teachers’ emotional exhaustion with an Implicit Association Test (IAT). We included the interpersonal teacher-student relationship (in terms of teacher agency and communion), teacher experience, and teacher gender as covariates in our analyses. Participants were 94 teachers in secondary education, vocational education, and teacher training for secondary education. Replicating findings from prior studies, hierarchical regression analyses showed that typical use of cognitive reappraisal, but not expressive suppression, was significantly related to lower levels of teachers’ emotional exhaustion. Teachers’ implicit attitudes towards emotion regulation versus emotion expression moderated the relationship between the use of emotion regulation strategies and emotional exhaustion, but only in a subsample with more experienced teachers. Teachers who showed more interpersonal agency in class and had more years of teaching experience reported lower levels of emotional exhaustion. Interpersonal communion and gender were not directly associated with feelings of exhaustion. Implications for teacher training and suggestions for future research are discussed.